Poluição sonora: estudo de caso do trânsito de veículos na subprefeitura de Pinheiros – São Paulo - Thiago França Shoegima; Alfredo Pereira de Queiroz Filho (Confins)
The aim of this paper is to compare the noise of traffic of the Subprefeitura of Pinheiros with their noise limits established by zoning law in São Paulo city. Three surveys were conducted between 2010 and 2011, in 40 different points in the studied area, during the morning. It was found that the averages of 39 points (97.5%) exceeded the noise limits of the municipal zoning and only one point (2.5%) presented a compatible value. The average noise measured was 70.7 dBA. This value is above all the limits defined by city´s acoustic map. Analysis of these results indicates at least two basic requirements: the development of systems for monitoring and controlling noise pollution and the review of public policies related to the transport system in the city of São Paulo.